Redefining Food Storage for the Future : A Multifaceted Approach to Zembag's Business Model Innovation and Scalability - Kočiš, Tomáš; Špaček, Miroslav, 1954-; Andera, Michal, 1984-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
The thesis looks at the role of a business model in innovation ecosystems, the methodology of business model innovation and its frameworks and link with strategy. The goal of this thesis is to create a new business model for Terpenix s.r.o. known under their brand name Zembag, unlocking new profitability and accelerating growth and adoption. This will be achieved by a mixed research method, consisting of literature review, data collection, interviews with stakeholders and ideation. The proposed business model will be validated by interview with the company’s founder and based on financial calculations. The thesis concludes with the presentation of the new business model and its minimum viable product and integration to facilitate a future pilot study.
Vedoucí práce: Miroslav Špaček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses